ANALISIS PENGARUH PENYERAPAN ANGKATAN KERJA DENGAN PENDEKATAN SEM-PLS - Manduapessy, Rulan (Journal of Economics and Regional Science, 2025)
This study aims to determine the factors that influence the absorption of fresh graduate labor force in Mimika Regency. The research method used is associative with the number of respondents in this study as many as 50 companies that employ fresh graduates. The data collection technique used a questionnaire and an analysis tool instrument, namely Partial Last Sql (PLS), obtained results that show that knowledge, skills, work motivation, and communication skills have a positive and significant effect on the achievement of fresh graduate labor force absorption in Mimika Regency